Pathways in the Pathophysiology of Coronavirus 19 Lung Disease Accessible to Prevention and Treatment - Eisenhut, Michael; Shin, Jae Il (Frontiers in Physiology, 2020)
Background In COVID 19 related lung disease, which is a leading cause of death from this disease, cytokines like tumor necrosis factor (TNF) may be pivotal in the pathogenesis. TNF reduces alveolar fluid absorption due to impairment of sodium and chloride transport required for building an osmotic gradient across alveolar epithelial cells which in the airways maintains airway surface liquid helping to keep airways open and enabling bacterial clearance and aids water absorption from the alveolar spaces. TNF can through rho-kinase disintegrate the endothelial and epithelial cytoskeleton and thus break up intercellular tight junctional proteins thus breaching the intercellular barrier preventing flooding of the interstitial and alveolar spaces with fluid. Hypotheses • Preservation and restoration of airway and alveolar epithelial sodium and chloride transport and the cytoskeleton dependent integrity of the cell barriers within the lung can prevent and treat COVID 19 lung disease. • TNF is the key mediator of pulmonary edema in COVID 19 lung disease Confirmation of hypothesis and implications: The role of a reduction in function of epithelial sodium and chloride transport could be tested by analysis of chloride levels in exhaled breath condensate and levels correlated with TNF concentrations. Reduced levels would indicate a reduction of the function of the cystic fibrosis transmembrane conductance regulator chloride channel (CFTR) and a correlation with TNF levels indicative of its involvement. Anti-TNF treatment with antibodies is already available and needs to be tested in randomised controlled trials of COVID 19 lung disease. TNF levels could also be reduced by statins, aspirin and curcumin. Chloride transport could be facilitated by CFTR activators including curcumin and phosphodiesterase-5 inhibitors. Sodium and chloride transport could be further regulated to prevent accumulation of alveolar fluid by use of Na(+)/K(+)/2Cl(-) cotransporter type 1 inhibitors which have been associated with improved outcome in adults ventilated for ARDS in randomised controlled trials. Primary prevention of coronavirus infection and TNF release in response to it could be improved by induction of antimicrobial peptides LL-37 and human beta defensin-2 and reduction of TNF production by vitamin D prophylaxis for the population as a whole.